Influence of Filler Content and Polymer Composition on the Properties, Morphology and Processing Parameters of Biodegradable Composites - Tomasik, Joanna Alicja; Garbacz, Tomasz; Tor-Świątek, Aneta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Biodegradable composites based on PLA, PHB and a PLA/PHB (80:20) blend with 0, 5 and 10 wt% wood fibers were injection molded into ISO 527 Type 1A specimens. Samples were produced on an Engel Victory 200/50 fast track injection molding machine using a two channel, uncooled mold. Density, Shore D hardness, tensile properties, unnotched impact strength and fracture surfaces were examined.
Keywords: biodegradable polymer composites; polylactic acid (PLA); poly(3-hydroxybutyrate) (PHB); wood fibers; injection molding